Obtención de queratina a partir de plumas de pollo, utilizando queratinasas producidas por Bacilus spp. - Machuca Loja, Geanina J (2015)
The objective of this research was to obtain keratin from the enzymatic hydrolysis of chicken feathers, using the Bacillus spp as producer queratinasas enzymes. Chicken feathers have mostly over 83% of a fibrous protein sulfur and secondary structure shaped folded sheet called beta keratin, also present in the beak, claws nails. This protein is insoluble in water and rich in amino acids such as cysteine, methionine, glycine, serine and alanine, as well as various mineral salts, which can be interesting to obtain alternative keratin hydrolyzate. The methodological research design was experimental, for which four (4) fermentations were performed, corresponding to a completely randomized experimental design, resulting consider two factors [substrate concentration and concentration of inoculum and two levels for each factor] ) resulting four treatments T1 = 18% of HPP 2 g / L inoculum, T2 = 18% of PPH 3 g / L inoculum, T3 = 23% of PPH 2 g / L inoculum and T4 = 23% of PPH 3 g / L inoculo. Este process is performed in an aerobic fermentor at room temperature, adjusting the pH (7.5) and measuring dissolved oxygen concentration (%). The criteria used to select the concentration of feathers culture medium (18 g / L and 23 g / L) and incubation temperature (room temperature) was based on previous studies with protease enzymes. Determining the concentration of total nitrogen in the medium was performed by UV-Visible spectrophotometry, by the method of persulfate digestion, the maximum concentration of nitrogen is reached in the treatment 2 (1.5%), which multiplied by protein factor of 6.25 gives a percentage of 9.4% protein in the hydrolyzed keratin, showing significant difference (p <0.05) the rest of the treatments after 24 hours hydraulic retention. In conclusion, the enzymatic hydrolysis of chicken feather meal using the Bacillus spp producing proteolytic enzymes as possible.